Use of Spiders (Araneae) as Indicator for Monitoring of Habitat Conditions in Tarai Conservation Area, India - Hore, Upamanyu; Uniyal, V. P. (Indian Forester, 2008)
The efficacy of spider as indicator of habitat conditions in Tarai Conservation Area was examined. To compare habitat specific spider communities, five vegetation types were sampled from March 2005 to August 2006 by using pitfall traps and other semi- quantitative collection methods along transects. Along with spider sampling 11 habitat variables on sampled transects for each habitat types were measured. Cluster analysis and subsequent indicator value analysis produced substantially different cluster numbers for the five habitat-specific spider communities. Indicator species of each habitat were identified and species found strongly influenced by canopy cover and moistures regime in the habitat.